Dynamic mechanical control of local vacancies in NiO thin films. (8th May 2018) - Seol, Daehee; Yang, Sang Mo; Jesse, Stephen; Choi, Minseok; Hwang, Inrok; Choi, Taekjib; Park, Bae Ho; Kalinin, Sergei V; Kim, Yunseok
Abstract: The manipulation of local ionic behavior via external stimuli in oxide systems is of great interest because it can help in directly tuning material properties. Among external stimuli, mechanical force has attracted intriguing attention as novel stimulus for ionic modulation. Even though effectiveness of mechanical force on local ionic modulation has been validated in terms of static effect, its real-time i.e., dynamic, behavior under an application of the force is barely investigated in spite of its crucial impact on device performance such as force or pressure sensors. In this study, we explore dynamic ionic behavior modulated by mechanical force in NiO thin films using electrochemical strain microscopy (ESM). Ionically mediated ESM hysteresis loops were significantly varied under an application of mechanical force. Based on these results, we were able to investigate relative relationship between the force and voltage effects on ionic motion and, further, control effectively ionic behavior through combination of mechanical and electrical stimuli. Our results can provide comprehensive information on the effect of mechanical forces on ionic dynamics in ionic systems.